First spin-resolved electron distributions in crystals from combined polarized neutron and X-ray diffraction experiments. (2014) - Deutsch, Maxime; Gillon, Beatrice; Claiser, Nicolas; Gillet, Jean-Michel; Lecomte, Claude; Souhassou, Mohamed
No abstract available